Evaluation of psychosocial and material support variables: impact of the First Step Project in Fortaleza, Ceará, Brazil (Research, Society and Development, 2020)
This article is the result of some findings from a master's dissertation that was completed in 2019 with the objective of evaluating the impacts that the First Step Project develops for young apprentices in the city of Fortaleza/CE, through the variables of material support and psychosocial. Thus, the sample collected for convenience consisted of 74 young people who participated in the First Step Project, in the Young Apprentice modality. It classifies as a study that has a pure purpose, quantitative approach and exploratory level. The results show that the Likert-type evaluation scale of the 19 items has satisfactory quality (Cronbach's α = 0.905 and total item correlation (0.37; 0.649)); measures 4 factors from an explained variance of 62.596%; and its greatest influence comprises factor 2 that deals with the application of the trainee's skills on the pre-professional field.